Escape From Cairo to Vienna: Çerkes Mehmed Bey’s Refuge Seeking in the Habsburg Empire - Ömer Gezer (Tarih Dergisi)
Çerkes Mehmed, a sovereign Mameluke bey of Ottoman Egypt, fled from Cairo in the spring of 1726 after losing his war of expansion against the Sublime Porte. He first fled to Tripoli, then to Algiers. During this time, he attempted to obtain an imperial pardon to return to Egypt, using both the influence of the Barbary states and French diplomacy in Istanbul, where no one heard his voice. Then, encouraged by the regents of Tripoli and Algiers, he sailed to Triest to ask Charles VI, the Habsburg Emperor, for protection and mediation with the Ottoman Sultan, and for his pardon. Bearing in mind that this could endanger the peace with the Ottomans and the Karl’s Mediterranean diplomacy, the Hofburg did not allow him to travel to Vienna. In fact, the agenda of Ottoman-Habsburg relations changed when it emerged that Çerkes Mehmed was seeking refuge with the Habsburgs, with Istanbul demanding extradition of the rebellious bey, or at least the refusal of his refuge. Based on the Austrian, Ottoman, and British archival documents, as well as his letters, this article focuses on the last years of Çerkes Mehmed, from his flight from Cairo to Vienna to his death at his war for power in Egypt, where he returned after being refused by the Habsburgs.